TTOOL: modelo para planejamento pedagógico e instrumentalização de professores no processo de ensino-aprendizagem e avaliação em educação online. - Ferreira, Hilcéa Santos (2016)
Education plays a core role in the development of individuals and communities. In the 21st century, with the advancement of Digital Information and Communication Technologies, the pedagogical strategies have been rethought and professionals need to continually enhance their competencies (knowledge, skills and attitudes) in a sustained lifelong learning effort. Technologies and the use of computers not only change the way students should learn, but also, the ways they can learn and what, how, where and when they learn. In this scenario, where flexibility is essential and the need for training and educational is growing, distance education presents itself as an important alternative for accessing knowledge, increasing educational offerings, as well as, expanding higher education in Brazil. The roles of the key players in this process, teachers, tutors and students, have changed, as well as their interactions and implicit intentions throughout pedagogical process. Within the task of planning education initiatives or training, instructional designers can help teachers in choosing instructional strategies that are most effective for achieving specific educational goals and facilitate learning, considering the multiple factors that influence the implementation of an educational enterprise. Thereby, this study presents the development of a model, named TTool, and its implementation through an expert system, SE_TTool, that provide teachers with a model for course planning, in which competencies, expected learning goals and outcomes are aligned with assessment activities and monitoring of student learning. The main goal is to represent transparency of expectations and clarity for teachers and students, assisting teachers, unaware of instructional design principles, in making decisions about the structure of their courses and in choosing activities and tools for monitoring and assessing students through coherent sets of criteria (rubrics), fostering the use of technology. TTool is based on the following pillars: development of competencies, dialogue (communication, interactivity and collaboration), student-centered learning and learning-by-doing. To provide a diagnosis on the use of the TTool model, a proof of concept was carried out in order to validate it through its implementation in a prototype expert system checking the feasibility of its implementation and exemplifying its use by instructional designers who were unaware of both the model and the system.